2015
DOI: 10.1016/j.gaitpost.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Gait variability in healthy old adults is more affected by a visual perturbation than by a cognitive or narrow step placement demand

Abstract: Gait variability measures have been linked to fall risk in older adults. However, challenging walking tasks may be required to elucidate increases in variability that arise from subtle age-related changes in cognitive processing and sensorimotor function. Hence, the study objective was to investigate the effects of visual perturbations, increased cognitive load, and narrowed step width on gait variability in healthy old and young adults. Eleven old (OA, 71.2 ± 4.2 years) and twelve young (YA, 23.6 ± 3.9 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 33 publications
3
67
2
Order By: Relevance
“…They found that ML visual perturbations significantly increased gait variability (+152% step width variability and + 131% step length variability) in older adults but not younger adults compared to the normal condition, suggesting that older adults depend more on visual feedback for whole‐body positioning. Older adults also walked with 5% shorter step length in the ML visual perturbation condition, a significant change compared to the no visual perturbations condition . Figure illustrates an example of a motion capture system using anatomically placed markers.…”
Section: Effects Of Visual Manipulations On Gait and Balance In Healtmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that ML visual perturbations significantly increased gait variability (+152% step width variability and + 131% step length variability) in older adults but not younger adults compared to the normal condition, suggesting that older adults depend more on visual feedback for whole‐body positioning. Older adults also walked with 5% shorter step length in the ML visual perturbation condition, a significant change compared to the no visual perturbations condition . Figure illustrates an example of a motion capture system using anatomically placed markers.…”
Section: Effects Of Visual Manipulations On Gait and Balance In Healtmentioning
confidence: 99%
“…Older adults also walked with 5% shorter step length in the ML visual perturbation condition, a significant change compared to the no visual perturbations condition. 45 Figure 3 illustrates an example of a motion capture system using anatomically placed markers. Similarly, Franz et al 46 studied old and young subjects who were instructed to walk on a treadmill at their preferred speed while viewing a speed-matched virtual reality hallway in the presence and absence of continuous ML visual perturbations.…”
Section: Visual Perturbationsmentioning
confidence: 99%
“…Walking balance control is especially dynamic, involving coordinated adjustments in posture (i.e., head and trunk stabilization) and foot placement from step to step (Bauby and Kuo, 2000; Kay and Warren, 2001; Donelan et al, 2004; Rankin et al, 2014). Particularly in unpredictable and challenging environmental conditions, these adjustments depend on the integration of reliable sensory feedback and the planning and execution of appropriate motor responses (O'Connor and Kuo, 2009; O'Connor et al, 2012; Francis et al, 2015; Franz et al, 2015, 2016; Goodworth et al, 2015). Accordingly, sensory and mechanical perturbations are increasingly used to study corrective motor responses in standing and walking and the onset and progression of balance deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, sensory and mechanical perturbations are increasingly used to study corrective motor responses in standing and walking and the onset and progression of balance deficits. Sensory perturbations may include those of visual (e.g., optical flow) (O'Connor and Kuo, 2009; O'Connor et al, 2012; Francis et al, 2015; Franz et al, 2015, 2016), somatosensory (e.g., tendon vibration) (Gurfinkel et al, 1976; Hay et al, 1996; Bove et al, 2003; Mullie and Duclos, 2014), or vestibular feedback (e.g., galvanic stimulation) (Day et al, 1993; Fitzpatrick et al, 1994; Bent et al, 2002; Dakin et al, 2007; Dalton et al, 2014), whereas mechanical perturbations most frequently incorporate support surface translations (Sinitksi et al, 2012; Aprigliano et al, 2016). Cortical activity and high-order cognitive processes are highly involved in the planning and execution of these motor responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation